FAKTOR RISIKO TERJADINYA ANEMIA PADA PEKERJA SPBU DI KOTA BAU-BAU - Asmayani Asmayani; Yusuf Sabilu; Ramadhan Tosepu; Adius Kusnan (NHM PRESS, 2021)
The prevalence of anemia in Indonesia is still quite high. The results show that the national prevalence of anemia in all age groups is 21.70%. The purpose of this study was to determine the factors that influence the risk of anemia in gas station workers in Baubau City. The type of research used is descriptive research with a quantitative approach. The population in this study were all gas station workers (fuel filling operators) in Baubau City with a total population of 65 people. The number of samples in this study was 65 people. The results of the study were analyzed using the SPSS version 16.0 program. There is an influence between exposure to benzene on the risk of anemia in gas station workers with a value of = 0.000 < value of = 0.05, There is no influence between age and the risk of anemia in gas station workers with a value of = 0.072 > the value of 0.05 = 0.05, There is an effect between age There is an influence between the use of PPE on the risk of anemia in gas station workers with a value of = 0.001 < = 0.05 and the most dominant variable influencing the occurrence of anemia in gas station workers in Baubau City is Benzene with an Exp (B) value of 42.112. Benzene has an effect of 42.112 on the incidence of anemia in gas station workers in Bau-Bau